Do prey shape, time of day, and plant trichomes affect the predation rate on plasticine prey in tropical rainforests?. (10th August 2022) - Weissflog, Anita; Markesteijn, Lars; Aiello, Annette; Healey, John; Geipel, Inga
Abstract: Predation can effectively limit insect herbivores with cascading effects on plant community composition and diversity of tropical rainforests. Assessing variation in predation is therefore important to understand the mechanisms structuring complex rainforest ecosystems. Variation in predation with time of day may provide herbivores with temporal enemy‐free space. Trichomes (plant hairs) may provide spatial enemy‐free space by increasing climbing resistance for walking arthropod predators and by scattering bat echolocation calls. Artificial model prey is commonly used to measure predation pressure on insect herbivores. Whether model prey shape is sufficient to deceive predators and whether attacks represent actual predation however remain unresolved. We used artificial, plasticine prey to assess temporal and spatial variation in predation in two Panamanian rainforests and tested whether model prey shape is as important for prey recognition by predators as often assumed. We assessed the effect of prey shape and size, time of day, and trichomes on predation by comparing attacks on caterpillar‐ and humanoid‐shaped figurines. We find higher nocturnal than diurnal predation in one but not the other forest, suggesting that herbivores may benefit from enemy‐free space during the day in some forests. We find no evidence for an effect of trichomes on predation in the two plant species tested. Equal attack numbers on caterpillar‐ and humanoid‐shaped objects challenge the idea that the visual resemblance of model prey alone is sufficient to deceive predators. We conclude that attacks on model prey represent a variety of responses to novel objects (e.g. exploration, aggression, possibly predation) and urge caution when interpreting their results. Abstract in Spanish is available with online material. Abstract : We used artificial, plasticine prey to assess temporal (day‐ versus nighttime) and spatial (pubescent versus glabrous host plant) variation in predation in two Panamanian rainforests. We compared attacks on caterpillar‐ and humanoid‐shaped figurines to test whether model prey shape is as important for prey recognition by predators as often assumed. We find higher nocturnal than diurnal predation in one but not the other forest and no evidence for an effect of trichomes on predation in the two plant species tested. Equal attack numbers on caterpillar‐ and humanoid‐shaped objects challenge the idea that the visual resemblance of model prey alone is sufficient to deceive predators. RESUMEN: La carrera armamentista entre los insectos herbívoros y sus plantas huéspedes afecta a la composición de las comunidades y a la diversidad de las selvas tropicales. La depredación presenta el principal riesgo de mortalidad para los insectos herbívoros y contribuye sustancialmente a estructurar los complejos ecosistemas de la selva tropical. Los insectos herbívoros pueden seleccionar los tiempos de actividad o las localidades en las que se reduce el riesgo de depredación. Los insectos herbívoros podrían seleccionar tiempos de actividad o lugares donde el riesgo de depredación es menor. Un espacio libre de enemigos temporal podría surgir de la variación en la depredación durante el día. Un espacio libre de enemigos espacial podría ser proporcionado por los pelos de las plantas, es decir, los tricomas. Los tricomas del tallo podrían disuadir a los depredadores artrópodos aumentando la resistencia de su desplazamiento en el ascenso y los tricomas foliares podrían dispersar la llamada de ecolocalización de los murciélagos. Usamos una presa artificial para evaluar la variación temporal y espacial de la depredación en dos áreas de bosques húmedos tropicales en Panamá y analizamos si el modelo de figuras de depredación es tan importante en el reconocimiento de la presa por los depredadores como frecuentemente se asume. Comparamos los ataques sobre los gusanos de plastilina, con formas naturales de diferentes tamaños, con figurines de plastilina, en forma de superhéroes humanos, y analizamos el efecto durante el día, con tricomas, con las formas de presa y el tamaño de la presa sobre la depredación. La tasa de depredación nocturna fue 3.5 veces mayor que la tasa de depredación diurna. Sostenemos que esta variación temporal en la depredación puede proporcionar a los herbívoros un espacio libre de enemigos durante el día. Los tricomas no afectaron a la depredación, lo que indica que las estructuras de la superficie de las plantas no parecen proporcionar a los herbívoros un espacio espacial libre de enemigos. La forma modelo de la presa no afectó a la depredación. Esta observación desafía a la idea de que la similitud visual con la presa modelo por sí sola es suficiente para engañar a los depredadores. Nuestro resultado de una mayor depredación nocturna en uno, pero no en el otro sitio de bosque sugiere que los cambios temporales en la composición de la comunidad de depredadores, que pueden variar entre los sitios de bosque, podrían impulsar la variación diurna de la depredación en una localidad específica. Los mismos números de ataque en orugas modelo y superhéroes indican que los ataques en presas modelo pueden representar una variedad de respuestas a objetos nuevos (por ejemplo, exploración, defensa o agresión), siendo la depredación solo una de ellas. Si bien los estudios de modelos de presas pueden proporcionar información sobre interacciones multitróficas que de otro modo serían difíciles de medir, recomendamos precaución al interpretar sus resultados.